Diagnostic value of bronchoalveolar lavage in children with nonresponding community-acquired pneumonia - Chih-Min Tsai; Kin-Sun Wong; Wei-Ju Lee; Kai-Sheng Hsieh; Pi-Lien Hung; Chen-Kuang Niu; Hong-Ren Yu (Elsevier, 2017)
Community-acquired pneumonia (CAP) is a common cause of morbidity and mortality in hospitalized children. In CAP, causative agents are seldom identified using noninvasive diagnostic procedures. For those children not responding to empiric antibiotic therapy, it is vital to identify the causative pathogens for further management. Methods: We aimed to determine the usefulness of identifying the causative agents by bronchoalveolar lavage (BAL) in hospitalized children with nonresponding CAP. Ninety children hospitalized for CAP and treated with empiric antibiotics but having persistent fever ≥48 hours were enrolled, and their BAL data were retrospectively reviewed. Results: Aerobic bacteria were isolated from 38 (42%) of 90 cultures, and anaerobic bacteria were isolated from eight (24%) of 33 cultures. The bacteria isolated most frequently were Streptococcus viridians (26.3%), Pseudomonas aeruginosa (23.7%), and Staphylococcus aureus (15.8%). Streptococcus pneumoniae was isolated from the BALs of only two children, and Haemophilus influenzae from none. For positive aerobic culture results, BAL results guided modifications of antibiotic regimens in 21 episodes (21 of 38, 55.3%). Conclusion: BAL results guided a change of antimicrobials in 55% of children with positive aerobic cultures (29% of all children in the study) and contributed to a high rate of successful therapy.